Psychological compatibility and its relationship to the psychological needs of high school students - Alhasani, Ibraheem Abutaleb Mohammed; Alsayed, Mohammed Ahmed Shbeir; Nasr, Fathy Mahdy Mohamed (Journal of Educational and Psychological Sciences, 2021)
The research aimed to identify the relationship between psychological compatibility and psychological needs of high school students in Al-Qunfudhah, and to verify the existence of an effect of the school stage on psychological compatibility and psychological needs, the study sample consisted (251) students in high stage school in Al-Qunfudhah, the researcher used the psychological compatibility scale and the psychological needs scale (the researcher's preparation), and the researcher relied on his study on the relational descriptive approach, the results of the study resulted in the following: There is a positive correlation between the degrees of the study sample in the psychological compatibility scale in all its dimensions. The results also showed that there were differences between the sample members on the dimensions of the psychological needs scale and the dimensions of psychological compatibility according to the specialty (scientific - literary). Based on these results, the researcher recommends that it is important to train students to seek psychological support in case he feels incompatible in any of the areas of compatibility, as well as to training teachers and student guides on modern methods of supporting students with a disorder of psychological compatibility.
Keywords: psychological compatibility; psychological needs; high school students